Sosialisasi dan Analisis Bahaya Hate Speech di Lembaga Kursus & Pelatihan AL-AMIN Tentang - Iswan Nurul M; Jamil Ulumudin; Rendi Alinurdin; Rifky Muhammad Shidiq; Syahrul Yanuar (Jurnal Pengabdian Literasi Digital Indonesia, 2022)
At this time, one of the things that dominates human life is the existence of social media. The free delivery of information, comments, and messages can trigger social media users to make hate speech. At the Al-Amin Course & Training Institute (LKP) which coincided in Garut, almost all of the training participants had social media, so socialization activities were established to prevent them from uttering hate speech. Hate speech is personal designations and epithets that are so vulgar that they can create problems for theory and practice directed against race, religion, ethnicity, gender or preference. Prior to the presentation of the material, a pre-test was carried out and after the training the material was given a post-test to the participants. The results of the pre-test and post-test scores increased understanding and knowledge by 18% related to hate material. From this activity, the training participants received material related to hate so that the trainees could accept and understand everything about hate on social media.